KETERLIBATAN ORANG TUA, REGULASI DIRI, AGRESIVITAS MEMPENGARUHI PERILAKU TOLERAN ANAK: PATH ANALYSIS - Yubaedi Siron; Rachmat Mulyono (Jurusan PIAUD IAIN Syekh Nurjati Cirebon, 2019)
Child-tolerant behavior becomes an important aspect of child development to be developed. The potential for future intolerance can be minimized if tolerant behavior is well stimulated in early age. The objective of this study is to analyze the effect of parental involvement, child self-regulation, and child aggression to the child tolerant behavior. The research used path analysis technique. There are 150 children at 5-6 years-old and 150 their parents in East Jakarta involved in this study taken by simple random sampling. The results of this study revealed: 1) There is no direct effect of parental involvement to the child tolerant behavior; 2) There is a direct effect of child's self-regulation to the child tolerant behavior; 3) There is no direct effect of child aggression to the child tolerant behavior; 4) There is a direct negative effect of parental involvement to the child aggression; 5) There is a direct negative effect of the child's self-regulation to the child aggression; 6) There is a direct effect of parental involvement to the child self-regulation.